The Concept of a Pumped Storage Power Plant - Narimanov Bahodir Absalamovich; Baratov Laziz (Scientific Trends, 2023)
This article discusses the principle of operation and convenience of a Pumped storage power plant (HPP), as well as its technical design.
Keywords: PSPP, pump, pump-turbines, generator mode, thermal power plants and nuclear power plants, transformer booth, water intake, swimming pool.